ELECTIVE COURSE AT THE THEORETICAL DEPARTMENT AS A BASIS FOR PROFESSIONAL COMPETENCIES FORMATION OF A PHYSICIAN - E. F. Barinov (Образование и наука)
Introduction. One of the problems of the higher school is mismatch of activities of the Theoretical and Degree Granting (main) Departments to form the students’ competencies. The use of fundamental knowledge in contents of professional preparation components quite often has formal character. The violation of integrity and continuity of training in higher education institution turns out to be the consequence of it. In medical educational institutions the situation is complicated by the fact that each of numerous clinical departments has its own specifics defining inquiries to the content of the particular theoretical discipline. The aim of the article is justify the need for designing elective courses at theoretical departments in medical universities, which enable future physicians to acquire both the fundamental knowledge and required professional competencies. Methodology and research methods. The framework of the article is based on activity, practice-oriented and competency-based approaches to education. When selecting educational material for elective courses, the foundations of contextual (motivational) approach to education, the method of expert evaluations, the dialectic principles of systemacity and variability of the educational material content, unity of integration and differentiation of fundamental knowledge were used. Results and scientific novelty. The author describes the experience of designing elective courses for students of various specialties and training programs at the Department of Histology, Cytology and Embryology of the Donetsk National Medical University named after M. Gorky. Since there are currently no general programs for Histology elective courses within the competency-based concept of education, their designing is a topical issue of Didactics. The principles of the content selection for such courses are formulated in accordance with their main purpose – cross-disciplinary integration of fundamental and applied knowledge. Practical significance. The publication findings could be useful for managerial personnel and lecturers of medical universities when designing integrated courses the content of which is interdisciplinary.